EFFECT OF ORGANIC FERTILIZER AND EM1ON GROWTH AND YIELD OF TWO LETTUCE CULTIVARS (LACTUCA SATIVA L.) ON GREENHOUSE CONDITIONS - SARHAN, TAHA Z.; MOHAMMED, GHURBAT H.; TELI, ZHIYAN A. (Journal of Duhok University, 2022)
The study was conducted to observed the effects of Organic fertilizer and EM1on growth and yield of two lettuce cultivars in the greenhouse conditions during 2011 growing season. The experiment was performed by Randomized Complete Block Design (RCBD) consisted of four levels of EM1 (0, 500, 1000, 1500) ml.l-1, Organic fertilizer (without and with fertilizer) and two lettuce cultivars (Syrian and Local cv.). The results showed that cultivar Syrian significantly increased plant height (cm), leaves number plant-1, and head circumference (cm) while Local cv. significantly increased stem length (cm), chlorophyll% and dry weight (g). Organic fertilizer increased head circumference (cm), head weight (kg) and total yield (t.ha-1). EM1 at concentration 1500 ml.l-1 significantly increased, plant height (cm), leaves number plant-1, head circumference (cm), dry weight (g), head weight (kg) and total yield (t.ha-1). The interactions among three factors caused positive significant differences in all vegetative and yield characteristics